Modeling and optimisation studies on the ultrasound-assisted extraction of phenolic compounds from Azadirachta indica - Patil, S.S. (Taylor and Francis Ltd., 2021)
The need for naturally occurring pharmaceutical compounds has long been a topic of interest. Azadiractin is a naturally occurring biopesticide in margosa species. Green chemistry principles are employed to conserve valuable resources and minimize ill effects on the environment. The present study reports the ultrasound-assisted extraction of the total phenolic content from Azadirachta indica leaves. The Taguchi technique was employed to optimize factors affecting the yield of the total phenolic content such as particle size (0.15â0.60 mm), temperature (25â55 Â°C), the solid to liquid ratio (1:20â1:50 g mLâ1), and irradiation time (15â60 min). The statistical analysis revealed that particle size had the most significant effect on the yield, followed by temperature, irradiation time, and the solid to liquid ratio in that order. The optimized conditions resulted in a maximum yield of 30 milligram gallic acid equivalent per gram plant material of the total phenolic content. The rate constant and effective diffusivity were determined by the first-order kinetic model and Fickâs second law of diffusion, respectively. The effective diffusivity evaluated under optimized experimental conditions was 6.85 Ã 10â12 m2 sâ1. Â© 2021 Taylor & Francis Group, LLC.